Graphene: Probing Bilayer Grain Boundaries in Large‐Area Graphene with Tip‐Enhanced Raman Spectroscopy (Adv. Mater. 7/2017). Issue 7 (February 2017) - Park, Kyoung‐Duck; Raschke, Markus B.; Atkin, Joanna M.; Lee, Young Hee; Jeong, Mun Seok
Abstract : A twisted stacking bilayer structure of grain boundaries in large‐area graphene is revealed by Mun Seok Jeong and co‐workers in article number 1603601 from high‐spatial‐resolution (<18 nm) correlated analysis of topography, near‐field scattering, and hyperspectral tip‐enhanced Raman spectroscopy (TERS) imaging. The demonstrated analytical results of bilayer grain boundaries deliver an informative guide toward the design of future graphene devices; furthermore, this approach will be generally applicable to a range of two‐dimensional materials beyond graphene.